Breaking challenges: queer perspectives on solutions to establish inclusive sexual-reproductive healthcare in Gauteng Province, South Africa - Seretlo, Raikane James; Mokgatle, Mathildah Mpata; Smuts, Hanlie (Frontiers in Sociology, 2024)
IntroductionIn South Africa’s diverse population, queer voices emerge as change agents, proposing new and critical solutions to reform sexual and reproductive healthcare services in the pursuit of inclusivity and equality. Our research aimed to explore and describe queer individuals’ perceptions and solutions for promoting sexual-reproductive healthcare services and needs (SRHSN) in Gauteng Province, South Africa.MethodologyAn explorative-descriptive study was performed for this research. A total of 22 queer individuals was recruited using respondent-driven sampling (RDS) within a queer-inclusive non-governmental organization (NGO) clinic in Gauteng Province, South Africa. Semi-structured interviews and an interview guide were utilized to collect data using English. Thematic content analysis was applied using NVivo 14.ResultsFour main themes and related sub-themes were revealed from the study including the creation of healthcare equity for queer individuals, empowering and supporting healthcare providers (HCPs) to enhance skills, knowledge, and expertise, raising awareness on queer-related issues, and different stakeholders’ involvement.ConclusionAs we navigate South Africa’s complex landscape of SRHSN for queer individuals, the crucial opinions and solutions offered by queer people not only challenge the status quo but also reveal an approach to a better, more equitable, empathetic, and accommodating healthcare system for everyone. Future studies should ensure the inclusiveness of queer individuals with the interest of improving their health not just for research outputs.